Asteroseismology of pulsating low-mass white dwarf stars - Ramos, Gabriel Lauffer (2024)
White dwarf stars are the most common final stage of stellar evolution, corresponding to 99% of all stars in the Galaxy. Around 10% of white dwarfs in the solar neighbourhood are low-mass (< 0.45M⊙) objects. In the case of low-mass white dwarfs, up to 70% of them are in binary systems. The total number of stars in such systems increases to 100% when extremely low-mass white dwarfs are considered. The pulsating low-mass white dwarf stars have stellar masses between 0.30 M⊙ and 0.45 M⊙ and show photometric variability due to gravity-mode pulsations. Within this mass range, they can harbour both a helium- and hybrid-core, depending if the progenitor experienced helium-core burning during the prewhite dwarf evolution. The eclipsing binary system SDSS J115219.99+024814.4 is composed of two low-mass white dwarfs with stellar masses of 0.362±0.014 M⊙ and 0.325±0.013 M⊙. The less massive component is a pulsating star, showing at least three pulsation periods of ∼1314 s, ∼1069 s, and ∼582.9 s. This opens the way to use asteroseismology as a tool to uncover its inner chemical structure, in combination with the information obtained using the light-curve modeling of the eclipses. By means of binary evolutionary models leading to helium- and hybrid-core white dwarfs, we computed adiabatic pulsations for ℓ = 1 and ℓ = 2 gravity modes with GYRE. We found that the pulsating component of the SDSS J115219.99+024814.4 system must have a hydrogen envelope thinner than the value obtained from binary evolution computations, independently of the inner composition. Finally, from our asteroseismological study, we find a best fit model characterised by Teff = 10 917 K, M=0.338 M⊙, MH = 10−6 M⊙ with the inner composition of a hybrid white dwarf.